Gregory Cromwell: Two Portrait Miniatures by Hans Holbein the Younger - Fitzgerald, Teri (The journal of ecclesiastical history, 2016)
This paper presents a probable identification of not one but two portrait miniatures of Gregory Cromwell, only son of England's only vice-gerent in spirituals, by Hans Holbein the Younger. The historical evidence has hitherto remained unconnected because of misunderstandings about Gregory's age, which are clarified here, and also thanks to the unexpected modern locations of the two relevant miniatures.